STRATEGI SWITCHING PREMI DALAM PENGUMPULAN DANA MASYARAKAT SEKTOR INFORMAL SEBAGAI UPAYA PENCEGAHAN KETERLAMBATAN PEMBAYARAN PREMI JAMINAN KESEHATAN NASIONAL - Intiasari, Arih Diyaning; Trisnantoro, Laksono; Hendrartini, Julita (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2017)
The increase in the budget deficit BPJS in the first 3 years of implementation JKN require special attention. One of the problems in the implementation of JKN is high late payment of premiums by the participants of the Non PBI Mandiri. The purpose of this study was to determine the participants' perceptions of Non PBI Mandiri to the recommendations transition strategy JKN premium payer. This study is a policy with qualitative descriptive approach. The study design used policy aims to draw up a recommendation is the Case Study on the phenomenon of late payment of premiums. Depth interviews with 11 informants participants Independent Non PBI done with purposive sampling quota system. The result showed that the presence of positive consequences as the public response to the concept of a transitional strategy premium payer. Participants claimed to be greatly assisted if the program was held because it can ease the burden of their medical expenses when his advanced age and does not have income again, providing peace in the certainty of change of insurer premiums in non-productive age. Conclusion of the study were breakthrough made in a transitional strategy premium payer has received positive responses from the public policy goals.